If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4y + 3x + 9y = 0 Reorder the terms: 3x + -4y + 9y = 0 Combine like terms: -4y + 9y = 5y 3x + 5y = 0 Solving 3x + 5y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5y' to each side of the equation. 3x + 5y + -5y = 0 + -5y Combine like terms: 5y + -5y = 0 3x + 0 = 0 + -5y 3x = 0 + -5y Remove the zero: 3x = -5y Divide each side by '3'. x = -1.666666667y Simplifying x = -1.666666667y
| 2Y-6=-34 | | z-3/5=4 | | (2*x/3*y)^5 | | y=98-2x^2 | | 2x^2-2x^2-12x= | | (4x-3)(5x+2)=0 | | 15x^3y^4-60xz^8=0 | | z-5/3=4 | | 81=y^2+2y^2 | | 3/5-z=4 | | x^2+4x+4=6+3x | | I/9-4=-23 | | 3/5-5/3=4 | | 3x^3-5x^2=6 | | 3a-2+5a-7= | | 3/5-5/3 | | ((3-(3/2x))^2) | | x-3/5=4 | | 5+(4m-9)= | | 124=y+3x^3 | | (3-(3/2x))^2 | | -3y-17=27-7 | | 5/3-z=4 | | x=8+-3y | | 2.5x+5y=35 | | W/-11+8=5 | | 1/3q=-7 | | 5/4x-7x=6 | | 5a-7a+2= | | 20-5(p-1)+3p=(2p-15) | | (3-3/2x)^2 | | 12-3z+2y-4x=0 |